Prototipo para medición de fuerza en pacientes con tenorrafia en el músculo flexor profundo de los dedos de la mano - Fajardo Sánchez, Guillermo Arturo (Universidad Antonio Nariño, 2024)
The hand is one of the most essential parts of our body, for this reason, it presents high rates of risk of suffering injuries, which arise from different causes, including improper or excessive use and blows. Among the great variety of injuries is that of the flexor tendons of the fingers, which produces significant limitation in the mobility of the fingers, since the flexor tendons are one of those responsible for the strength and grip of the hand, Therefore, when suffering an injury, surgical treatment is commonly required, followed by mobilization processes of the limbs to achieve a complete recovery of movement.